2010
DOI: 10.1039/b914409a
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of surface water quality in the Cértima River basin, central Portugal

Abstract: The Cértima River is the principal source of water flowing into the Pateira de Fermentelos, which is one of the largest natural lakes of the Iberian Peninsula and has elevated conservation value. This study aims at a more comprehensive understanding of the spatial pattern in water quality and, thus, pollution problems in and especially upstream of the Pateira, including a comparison with a prior study in 2003. To this end, surface water samples were collected, in May 2007, at 29 sites covering the basin's four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A key driver was the enactment of legislation in 1938 which encouraged afforestation of areas classified as "uncultivated/wasteland", which often consisted of areas of matos (shrublands), mountain ranges, and sand dunes (Coelho et al, 1995;Estêvão, 1983;Ferreira et al, 2010;Jones et al, 2011;Silva et al, 2004). The primary species planted during this earlier period was Pinus pinaster, and beginning in the 1970s Eucalyptus globulus became the preferred species due to its faster growth and higher profitability for use in the paper pulp industry.…”
Section: Watershed Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key driver was the enactment of legislation in 1938 which encouraged afforestation of areas classified as "uncultivated/wasteland", which often consisted of areas of matos (shrublands), mountain ranges, and sand dunes (Coelho et al, 1995;Estêvão, 1983;Ferreira et al, 2010;Jones et al, 2011;Silva et al, 2004). The primary species planted during this earlier period was Pinus pinaster, and beginning in the 1970s Eucalyptus globulus became the preferred species due to its faster growth and higher profitability for use in the paper pulp industry.…”
Section: Watershed Descriptionmentioning
confidence: 99%
“…Across a number of catchments with winter-dominant rainfall, Brown et al (2005) found that afforestation led to much larger proportional reductions in summer flows compared to winter flows, which they attributed to the afforestation-induced changes in interception and evapotranspiration. Among these catchments, those of Gallart et al (2001) and Lewis et al (2000) demonstrated the importance of soil depth in controlling the hydrological response of Mediterranean mountain catchments in the Pyrenees and California, respectively. Other studies with somewhat similar site conditions (i.e., Bari et al, 1996;Van Lill et al, 1980) were conducted at very different temporal and spatial scales than the present study, making comparisons to their findings difficult.…”
Section: Streamflow Trendsmentioning
confidence: 99%
“…A unique feature of buried-valley sedimentary architecture data is the presence of gravel-dominated facies such as open-framework gravel (OFG) crossstrata, which have negligible sand content and a unimodal grain size distribution (d 50 > 2 mm). As a result, the conductivity of OFG facies can reach to up to 10 3 darcys (Ferreira et al, 2010;Jussel, 1989;Klingbeil, Kleineidam, Asprion, Aigner, & Teutsch, 1999;Lunt, Bridge, & Tye, 2004). The formation and preservation of OFG cross strata is common, especially along gravelly riverbeds (Lunt & Bridge, 2007), where they may strongly control hyporheic exchange by channelling flow wherever they intersect the channel boundary (Zhou, Ritzi, Soltanian, & Dominic, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The annual rainfall varies from 1103 mm in the lower foothills of the mountain and can reach up to 2370 mm in the higher mountain zones (SNIRH, 2022). The mean temperature differs from 14°C in January to 24 in August in the lower foothills and varies from 9°C in January to 19°C in August in the higher zones (Boulet et al, 2015; Ferreira et al, 2010; Ribeiro, 2006).…”
Section: Methodsmentioning
confidence: 99%